KEGIATAN WIRAUSAHA 34 KULINER KHAS INDONESIA MAHASISWA PENDIDIKAN AKUNTANSI UNIVERSITAS PGRI PALEMBANG - Nova Pratiwi; Chandra Kurniawan (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
This study examines entrepreneurial activities among university students, aligned with the need to prepare students in solving contemporary work and environmental development. This study aims to explore the entrepreneurial activities of 34 Indonesian culinary university students of Accounting Education at University of PGRI Palembang in the fourth semester of the academic year 2018/2019. This research is a qualitative study using interview and observation techniques. The result shown 4 themes discussed; they were small business management, buyer response, opportunities and challenges for business development. These four themes are useful for understanding how to start a business with small capital, especially among university students optimally